Experimental Evidence on Tax Incentives and the Demand for Capital Investments - Davis, Jon S.; Swenson, Charles W. (The Accounting Review, 1993)
[Since the pioneering work of Hall and Jorgenson (1967), numerous studies (e.g., Bischoff 1971; Chirinko and Eisner 1982; and Coen 1971) have examined the effect of attempts by the tax authority to influence investment decisions through accelerated depreciation or investment tax credits (ITC). This body of research has been fraught with econometric estimation problems, and consequently has failed to provide a clear picture of the effect of tax policies on capital investment. In a review of the literature, Chirinko (1986, 151) concludes that "[w]hile investment may respond significantly to variations in tax parameters, it appears to this author that the supporting empirical evidence has yet to be generated." At the core of the difficulties in the econometric research paradigm is the operationalization of the neoclassical investment function itself. Chirinko (1986) notes that numerous inherent difficulties are introduced, including (1) estimations of the purchase cost of a unit of capital, financial cost of capital net of inflation, rate of depreciation of the capital good, rate of income taxation, rate of investment credit, discounted value of depreciation allowances, net cost of debt finance, and the like; and (2) the inability to control for firms' expectations regarding output, and hence the marginal product of capital. These difficulties highlight the general limitations of econometrics in certain settings. This sentiment was echoed by Chirinko and Eisner (1983, 139) when they concluded that, in the neoclassical tax policy arena, "one can get almost any answer one wants by making sure that the chosen model has specifications appropriate to one's purpose." In response to the inconclusive econometric evidence regarding the effect of tax incentives on capital investment, we adopt an alternative approach in this study, using laboratory markets to overcome the limitations noted above, thereby providing a controlled empirical test of neoclassical predictions. Although the results of our experiments provide no evidence regarding the real-world dollar responses of investment to income tax accounting subsidies, some insight into the ability of theory to predict more general aspects of taxpayer investment behavior is provided. Specifically, the research question addressed is whether capital investment increases when depreciation or investment credits allowed by the tax system result in more rapid deductions than true economic depreciation. Although this question follows directly from neoclassical predictions, we relax the assumption of price taking to permit the more realistic consideration of market price adjustments. The results of our experiments do not support the neoclassical prediction that depreciable asset investment will increase in response to accelerated tax depreciation or to investment tax credits. Demand was unresponsive to tax incentives because the prices of depreciable assets were bid up. That is, tax benefits were captured to some extent by factor suppliers. From a theoretical perspective, the study's results provide a "piece of the puzzle" in light of conflicting or nonexistent econometric evidence. In section I, a description of the experimental setting and administration is provided. Theoretical predictions of investment price and quantity are then derived from our experimental operationalization of a production economy in section II. Finally, results and conclusions are presented in sections III and IV, respectively.]